2006
DOI: 10.1038/sj.tpj.6500394
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-responsive genes: identification of transcription factors and their role in metabolomics

Abstract: Transcription factors (TFs) and their combinatorial control on cis-regulatory elements play critical role in the co-expression of genes. This affects the interaction of genes in the transcriptome and thus may affect signals that cascade through cellular pathways. Using a combination of bioinformatic approaches, we sought to identify such common combinations of TFs in a set of ethanol-responsive (ER) genes and assess the role of ethanol in affecting multiple pathways through their co-regulation. Our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 73 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Sp1 has been reported to regulate a group of "ethanol-responsive genes" (25). Sp1 also participates in the transcriptional regulation of several folate-requiring enzymes, including serine hydroxymethyltransferase (SHMT) and dihydrofolate reductase (DHFR) (24,26,27).…”
Section: Figmentioning
confidence: 99%
“…Sp1 has been reported to regulate a group of "ethanol-responsive genes" (25). Sp1 also participates in the transcriptional regulation of several folate-requiring enzymes, including serine hydroxymethyltransferase (SHMT) and dihydrofolate reductase (DHFR) (24,26,27).…”
Section: Figmentioning
confidence: 99%
“…A detailed discussion of region-specific regulation of CREB as it relates to behavioral phenotypes is presented in Section 6 but is introduced here in the context of cellular signaling. An in silico analysis of promoter elements in ethanol responsive genes has identified CREB as a potential mediator of ethanol effects on gene expression (Uddin and Singh 2007). Using mice expressing LacZ under a CRE, an acute exposure to ethanol increased CRE-mediated gene transcription (Asyyed et al, 2007) in NAc, PFC, Septum, BNST, Lateral Habenula, BLA, PVN, hippocampus, VTA and SN, in addition to hypothalamic nuclei.…”
Section: Effects Of Etoh On Bdnf Signalingmentioning
confidence: 99%
“…It has been shown that glucocorticoid-induced phosphorylation of CREB is dependent upon serine/threonineprotein kinase, SGK 37 , and SGK3 (aka CISK) is also a member of this module. Conversely, CREB has been implicated in the regulation of SGK3 during apoptosis 38 , and CREB has also been suggested to regulate the following module members: TNFSF15 (aka VEGI), HSD17B7, POLK, IL-18, DUSP19, RSAD2, ICAI (aka ICA69), KLHL28 (aka BTBD5), SLC5A8, and ZNF667 (aka MIPU1).…”
Section: Discussionmentioning
confidence: 99%